Meta-Synthesis: The Use of Augmented Reality Technology as A Mathematics Learning Media - Laely Maghfiroh; Scolastika Mariani; Arief Agoestanto (EduMa: Mathematics education learning and teaching, 2024)
This study aims to review, analyze and classify articles that contain literature related to the use of augmented reality technology as a mathematics learning medium. Using meta-synthesis methodology, this research systematically reviews and interprets findings from various articles related to the integration of AR in mathematics education. Through extensive searches in the Scopus and Sinta databases, 15 relevant articles were selected based on predetermined inclusion criteria, including year of publication (2018-2023), focus on mathematics learning in schools, and the presence of AR output images. Conducting a literature review with specific keywords ('Augmented Reality in mathematics learning'). The analysis reveals AR applications/modules, visualizations, and worksheets as prevalent AR outputs in math learning. In particular, Unity 3D and Vuforia excel among diverse development tools, showcasing flexibility. The discussion underscores AR's potential for intuitive math visualizations, enhancing learning experiences, and improving comprehension of complex concepts. The main characteristics of AR are virtual environments, real-time interactivity, and 3D representation, with an attractive design that makes a positive contribution to mathematics education.